Jarak Kekuasaan Sebagai Pemoderasi Pengaruh Keadilan Organisasional Terhadap Komitmen Karyawan Pada Supervisor (Studi pada Sebuah Perusahaan Batik di Surakarta) - Runing, Hunik Sri (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2011)
This research was conducted to analyze 1) influence of procedural and distributive justice to employee commitment to supervisor, 2) moderation role of the power distance orientation to the influence of procedural and distributive justice to employee commitment to supervisor. Hypothesis testing was using moderated regression analysis. Using 150 samples, the result indicates that 1) procedural and distributive justice has a significant effect on employee commitment to supervisor, 2) power distance orientation moderates the influence of procedural and distributive justice to employee commitment to supervisor.